Perlindungan Data Pribadi dalam Implementasi E-Notary - Donny Marbun; Nawal Karimah; Pandu Pramono; Radius Prayogo; Ricky Alfin Ramadha (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The development of technology has encouraged the implementation of e-notary in notarial services for greater efficiency. However, its application raises issues regarding personal data protection. This study aims to analyze legal regulations and protection efforts in e-notary implementation. The results show that although personal data protection law exists, specific regulation on e-notary remains inadequate. Therefore, regulatory harmonization and stronger security systems are required to ensure data protection and legal certainty.